2010
DOI: 10.1371/journal.pone.0013078
|View full text |Cite
|
Sign up to set email alerts
|

Postural Strategies and Sensory Integration: No Turning Point between Childhood and Adolescence

Abstract: In this study, we investigated the sensory integration to postural control in children and adolescents from 5 to 15 years of age. We adopted the working hypothesis that considerable body changes occurring during these periods may lead subjects to under-use the information provided by the proprioceptive pathway and over-use other sensory systems such as vision to control their orientation and stabilize their body. It was proposed to determine which maturational differences may exist between the sensory integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
47
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 49 publications
(65 reference statements)
7
47
1
4
Order By: Relevance
“…This is in line with our hypothesis that athletes have a different model of sensory integration, as compared to the nonathletes. The visual dependence of non-athletes supports the findings of Viel et al (2009) and Mallau et al (2010), which showed that vision plays a predominant role in adolescents' control of orientation and body stabilization, most probably due to the transient disturbances in proprioception caused by fast growth of the body parts.…”
Section: Discussionsupporting
confidence: 82%
“…This is in line with our hypothesis that athletes have a different model of sensory integration, as compared to the nonathletes. The visual dependence of non-athletes supports the findings of Viel et al (2009) and Mallau et al (2010), which showed that vision plays a predominant role in adolescents' control of orientation and body stabilization, most probably due to the transient disturbances in proprioception caused by fast growth of the body parts.…”
Section: Discussionsupporting
confidence: 82%
“…When visual information was not available, all of the groups behaved in the same way and differed only from adults in terms of VM, even though there was a decreasing trend; as for sX, the group of 6-year-olds differed from the groups of 11 years and above. Data obtained in Ec condition may be explained by the visual predominance in children already reported by many authors [3,8,9].…”
Section: Discussionmentioning
confidence: 63%
“…Postural control requires the organization and integration of somatosensory, visual and vestibular inputs by the central nervous system and the motor control process involved in executing musculoskeletal responses that keep the body within its limits of stability [1]. children's balance control is less developed as compared to adults and postural stability improves progressively with age from childhood to adulthood [2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The fundamental mechanisms behind postural control (e.g. sensorimotor development and functional ability) are formed and modified between childhood and adolescence through physical activity2. The developmental process of postural control involves several phases such as building repertoires of different postural strategies and learning how to apply these strategies to different environments through exploration34.…”
mentioning
confidence: 99%